Suffering time : philosophical, kabbalistic, and ḥasidic reflections on temporality - Wolfson, Elliot R. (Leiden ; Boston : Brill, 2021)
"The conception of time elicited by Wolfson from a host of philosophical and mystical sources-both Jewish and non-Jewish-buttresses the contention that it is precisely structural invariability that engenders interpretive variation. This hermeneutical axiom is justified, in turn, by the presumption regarding the cadence of time as the constant return of what has always been what is yet to be"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 06, 2021).
eBooks on EBSCOhost
Keywords: Time; Time -- Religious aspects -- Judaism; Jewish philosophy; Temps; Philosophie juive; time; Jewish philosophy; Time; Time -- Religious aspects -- Judaism